Summary of taxonomy changes ratified by the International Committee on Taxonomy of Viruses (ICTV) from the Animal DNA Viruses and Retroviruses Subcommittee, 2025 - Varsani, Arvind; Abd-Alla, Adly M M; Arnberg, Niklas; Bateman, Kelly S; Benkő, Mária; Bézier, Annie; Biagini, Philippe; Bojko, Jamie; Butkovic, Anamarija; Canuti, Marta; Celer, Vladimír; Drezen, Jean-Michel; et al. (Journal of general virology, 2025)
The International Committee on Taxonomy of Viruses (ICTV) holds a ratification vote annually after review of newly proposed taxa by ICTV Study Groups and members of the virology community. In March 2025, the vote outcome of the 11 proposals within the mandate of the Animal DNA Viruses and Retroviruses Subcommittee was made public. Here, we provide a summary of the newly accepted proposals. These include reorganization of taxa in the realm , classification of the 'polinton-like' viruses into a new family ( ) within a new order ; establishment of a new phylum ( ) in the kingdom ; the establishment of a new family called with two new genera and three new species; the addition of four new genera in the family with 70 new species; and the addition of 85 new species in the families ( =16), ( =5), ( =5), ( =55) and ( =4). Also, in the family , 11 species were renamed to comply with the binomial requirement for species names.